2015
DOI: 10.1007/s00253-015-6533-1
|View full text |Cite
|
Sign up to set email alerts
|

Production and transcriptional regulation of proanthocyanidin biosynthesis in forage legumes

Abstract: Proanthocyanidins (PA), also known as condensed tannins, contribute to important forage legumes traits including disease resistance and forage quality. PA in forage plants has both positive and negative effects on feed digestibility and animal performance. The analytical methods and their applicability in measuring the contents of PA in forage plants are essential to studies on their nutritional effects. In spite of important breakthroughs in our understanding of the PA biosynthesis, important questions still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 109 publications
(143 reference statements)
0
23
0
Order By: Relevance
“…PA accumulation in legume species is a complex, multigenic trait, with several, and likely species-specific, MYB factors that act within the MBW complex either as activators or repressors (Paolocci et al 2011;Albert 2015;Zhou et al 2015). Yet, the MBW complex is a gene network regulated by developmental signals and environmental determinants (Xie et al 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PA accumulation in legume species is a complex, multigenic trait, with several, and likely species-specific, MYB factors that act within the MBW complex either as activators or repressors (Paolocci et al 2011;Albert 2015;Zhou et al 2015). Yet, the MBW complex is a gene network regulated by developmental signals and environmental determinants (Xie et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…(Yoshida et al 2010a;Verdier et al 2012;Hancock et al 2012). Nevertheless, studies in A. thaliana and other model species have shown that the accumulation of flavonoids is finely orchestrated by numerous regulatory genes, with MYB members of the MBW complex that act either as activators or repressor (Xu et al 2015;Zhou et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of CTs have been demonstrated in only support the primary plant metabolism (Haslam, 1981). It is now well established that CT synthesis is under genetic control (Szczyglowski and Stougaard, 2008;Scioneaux et al, 2011;Cheynier et al, 2013;Escaray et al, 2014) and that expression depends on the plant species and plant parts (Larkin et al, 1997;Gebrehiwot et al, 2002;Abeynayake et al, 2012;Ferreyra et al, 2012;Hancock et al, 2012;Verdier et al, 2012;Cheynier et al, 2013;Harding et al, 2013;Mouradov and Spangenberg, 2014;Pérez-Díaz et al, 2014;Zhou et al, 2015;Zhu et al, 2015;Chezem and Clay, 2016).…”
Section: Roles Of Tannins In Plants and Challenges To Harnessing Theimentioning
confidence: 99%
“…Members of these groups are involved in several processes related to plant development [44]. In G4, MYB proteins from banana (MaMYB76 and MbMYB49) clustered with AtMYB04 (Figure 4), which is involved in flavonoid biosynthesis [50,51]. Similarly, AtMYB5 (shared clade with MaMYB17 and MbMYB135 in G5) is involved in regulating PA biosynthesis [52][53][54].…”
Section: Expression Profile Of Myb Genes During Fruit Ripeningmentioning
confidence: 99%